Penerapan Metode Eksperimen dalam Pembelajaran IPA untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas VI di SD Negeri Sukasari 1 - Dede Supriadi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study examines the effectiveness of the experimental method in improving the learning outcomes and learning motivation of third-grade elementary school students in science subjects. The research employed a quasi-experimental design with a pretest-posttest control group design, involving an experimental group taught using the experimental method and a control group taught with conventional methods. Data were collected using tests, questionnaires, and observation sheets. The findings reveal that the experimental method significantly enhances both learning outcomes and motivation compared to conventional methods. Statistical analysis using t-tests showed a significant difference (p < 0.05) between the experimental and control groups in terms of posttest scores and motivation levels. The experimental method proved effective in promoting active student engagement, deeper conceptual understanding, and intrinsic motivation. This method is recommended as a strategy to improve science learning quality in elementary schools.